2008 International Workshop on Content-Based Multimedia Indexing 2008
DOI: 10.1109/cbmi.2008.4564978
|View full text |Cite
|
Sign up to set email alerts
|

Toward emotion indexing of multimedia excerpts

Abstract: Multimedia indexing is about developing techniques allowing people to effectively find media. Content-based methods become necessary when dealing with large databases. Current technology allows exploring the emotional space which is known to carry very interesting semantic information. In this paper we state the need for an integrated method which extracts reliable affective information and attaches this semantic information to the medium itself. We describe SAMMI [1], a framework explicitly designed to fulfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 12 publications
(16 reference statements)
0
23
0
1
Order By: Relevance
“…Additionally, we study the applicability of several fusion schemes to further improve upon the results obtained with the individual modalities. Our results show that both unimodal approaches as well as the proposed combined system compare favorably with state-of-the-art techniques from the literature [9,12,13,14].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Additionally, we study the applicability of several fusion schemes to further improve upon the results obtained with the individual modalities. Our results show that both unimodal approaches as well as the proposed combined system compare favorably with state-of-the-art techniques from the literature [9,12,13,14].…”
Section: Introductionmentioning
confidence: 63%
“…. Confusion matrices for all 5 folds of our cross validation procedure generated using the presented audio sub-system Video SAMMI framework [12,24] 28.0 / Video sub-system [13] 37.0 / LBPs+HMMs [14] 37 …”
Section: Audio-video Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subtle exchange of glances between Elizabeth and her father would be readily apparent to most human observers, but it is unlikely that a computer processing a video of the scene would be able to recognise their meaning. Furthermore, while the double-entendre in Mr Bennett's remark would be clear to most human listeners, algorithmic recoginition of this or other modes of speech are in their infancy (Paleari & Huet, 2008). Other research communities are developing means to communicate such semantic information (whether computed or manually generated) in ways that are able to transcend the original context of the information.This work-originating from Knowledge Representation, but more popularly known as the Semantic Web-has provided languages such as the Resource Description Framework (RDF) (Beckett, 2004) and Web Ontology Language (OWL) (Dean & Schreiber, 2004) which can be used to express concepts in such a way that "this picture has many buildings" may also imply that "it is a cityscape", and "it contains man-made objects."…”
Section: Introductionmentioning
confidence: 99%
“…Paleari et al [69] carried out both decision and feature-level fusion. They experimented with the eNTERFACE dataset and showed that decision-level fusion outperformed feature-level fusion.…”
Section: Multimodal Fusionmentioning
confidence: 99%